Analisis Nilai Risiko Portofolio Optimum Pada Reksadana Campuran Dengan Pendekatan EWMA - Pratiwi, Noviana (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
Value at Risk (VaR) is one of the risk measurement techniques and is considered a standard method of measuring risk. EWMA is one method to find standard deviation value of Conditional Variance which used to calculate the VaR. Investors use VaR to determine the risk level. VaR defined as the estimated loss of portfolio with a certain level of confidence. A portfolio composed of several mixed mutual funds. Of the four mutual funds only two mutual funds that can be arranged to get an optimum portfolio, 20% of mutual funds Kresna Flexima and 80% Nikko BUMN Plus. Portfolio VaR is calculated by EWMA method because it found the existence of conditional Variance. With a 95% level of trust and decay factor in accordance with the proposed risk metrics of 0.94 for daily data than obtained the VaR value of 0.26221011. This means that the maximum losses that may be received by investors amounted to 26.22% if investors invest in assets recommended by the optimal portfolio. This level of risk will be used by investors to control investment risk.Â Keyword: VaR, EWMA, Portofolio Optimum, Reksadana